Changing USA national trends for adrenalectomy: the influence of surgeon and technique. (27th June 2014) - Monn, M. Francesca; Calaway, Adam C.; Mellon, Matthew J.; Bahler, Clinton D.; Sundaram, Chandru P.; Boris, Ronald S.
<x xml:space="preserve">Abstract</x> Objective To explain differences over time between operative approach and surgeon type for adrenal surgery in the USA. Patients and methods A retrospective cohort analysis was performed on all patients undergoing adrenalectomy between 2002 and 2011 using the Nationwide Inpatient Sample. Patients undergoing concurrent nephrectomy were excluded. Surgeon specialty was only available for 2003–2009. Descriptive analyses and multivariable logistic regression models were used to assess variables associated with minimally invasive surgery (MIS) and urologist‐performed procedures. Results In all, 58 948 adrenalectomies were identified. A MIS approach was used in 20% of these operations. There was a 4% increase in MIS throughout the study period (P < 0.001). Cases performed at teaching hospitals were more likely to be MIS (odds ratio [OR] 1.47, P < 0.001). We were able to identify surgical specialty in 23 746 cases, of which 60% were performed by urologists. Cases performed in the Midwest compared with Northeast were at increased adjusted odds of being performed by urologists (OR 1.38, P = 0.11). Despite most cases being performed by urologists, adrenalectomy by urologists showed a 15% annual decrease over the analysed period (P < 0.001). Conclusions The use of a MIS technique to perform adrenalectomy is increasing at a slower rate compared with most other surgical extirpative procedures. Further investigation to explain the decreased performance of adrenalectomy by urologists is warranted.